Is there a relationship between maximal grip strength and racquetball success? A pilot study - Layton, J. S.; DeBeliso, M. (Athens Journal of Sport, 2017)
Grip strength has proven to have a positive effect on sports performance in which a sport implement is grasped in the hand. Racquetball athletes are constantly in search of ways to find advantages over their competition and there is a paucity of research regarding the role of grip strength and racquetball performance. Purpose: This study sought to find the relationship between maximal grip strength of the dominant hand and success (in the context of an amateur racquetball tournament) in the sport of racquetball. Methods: Racquetball tournament players were recruited to participate in the study prior to the beginning of the tournament. Each participant was asked to perform at least three maximal isometric grip strength measurement trials using a Jamar Handgrip Dynamometer and the average of the three highest grip strength readings was recorded. The participants then went on to play in their groups in the racquetball tournament at the Utah Summer Games (USG). Following the tournament, the USG racquetball organizer provided researchers with the full results of the racquetball tournament. Results: Because of the limited number of female participants in the study only the data concerning male participants was statistically analyzed. Due to the large number of sub groups in the tournament, the data were analyzed as those who finished in 1st place versus those who finished below first place. An independent t-test indicated that there was not a significant difference in grip strength between group winners and the other competitors. Discussion: Although the results of this study did not show a significant difference in grip strength between those who succeeded in tournament play and those who did not, the results are important to the overall discussion of the role that grip strength plays in racquet sports, most specifically racquetball. This data can serve as a launching point for further research regarding grip strength and racquetball. Conclusion: Within the parameters of this study, it does not appear that grip strength plays a significant role in winning and losing in racquetball tournament competition